ANALYSIS OF THE EFFECTIVENESS OF USING VIDEOTRON AS AN EDUCATIONAL MEDIUM FOR WASTE REDUCTION AND IMPROVING PUBLIC HEALTH IN CENTRAL BANJARMASIN : VIDEOTRON AS AN EDUCATIONAL - Mutia Rahmi; Nadya Putri; Novea Leta; Muhammad Bayu Rezki; Zaqyyah Huzaifah; Afiatun Rahmah (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2026)
Background: The waste problem in Banjarmasin City, particularly in Central Banjarmasin, remains a serious challenge that impacts environmental quality and public health. Low public awareness and knowledge regarding waste management contribute to environmental pollution and increase the risk of environmental-based diseases. One effort undertaken by the local government is the use of digital media in public spaces, such as Videotron, as a means of educating people about waste reduction and promoting environmental health. This study aims to analyze the effectiveness of using Videotron’s as an educational medium in increasing public knowledge and its contribution to environmental health awareness in Central Banjarmasin. Methods: This study used a qualitative approach with a descriptive-analytical design. Data were collected through in-depth interviews, field observations, and documentation of residents exposed to Videotron displays, as well as government officials and media managers. Data analysis was carried out through data reduction, data presentation, and thematic conclusion drawing. Results: The study found that Videotron had visual Appeal and Attention-Grabbing Ability, could Increasing Knowledge about Waste Management, and it could contribute to Environmental Health Awareness. Conclusion: Videotron is useful as an educational medium for waste reduction and improving public health in Central Banjarmasin.